Modellbasiertes Testen bei der Entwicklung einer IKT-Infrastruktur für Elektromobilität - Güldali, Baris; Rose, Mirko; Teetz, Alexander; Flake, Stephan; Rust, Carsten

On-the-Fly Computing: Automatic Service Discovery and Composition in Heterogeneous Domains - Huma, Zille; Gerth, Christian; Engels, Gregor (Computer Science - Research and Development)

On Network Application representation and controller independence in {SDN - A. Aranda-Gutierrez, Pedro; Karl, Holger; Rojas, Elisa; Leckey, Alec (2015 European Conference on Networks and Communications, EuCNC 2015, Paris, France, June 29 - July 2, 2015)

Error characterization of multi-access point WSNs in an aircraft cabin - Blanckenstein, Johannes; Nardin, Cristina; Klaue, Jirka; Karl, Holger (IEEE International Conference on Communication, ICC 2015, London, United Kingdom, June 8-12, 2015, Workshop Proceedings)

Topology model to generate realistic latency for simulations - Schwabe, Arne; Karl, Holger (2015 IEEE International Conference on Communications, ICC 2015, London, United Kingdom, June 8-12, 2015)

Anticipatory Download Scheduling in Wireless Video Streaming with Uncertain Data Rate Prediction - Dräxler, Martin; Blobel, Johannes; Karl, Holger (8th IFIP Wireless and Mobile Networking Conference, WMNC 2015, Munich, Germany, October 5-7, 2015)

Extending Hadoop's Yarn Scheduler Load Simulator with a highly realistic network & traffic model - Wette, Philip; Schwabe, Arne; Splietker, Malte; Karl, Holger (Proceedings of the 1st IEEE Conference on Network Softwarization, NetSoft 2015, London, United Kingdom, April 13-17, 2015)

Kurzportrait zum Standortkonzept des Berufskollegs West der Stadt Essen - Frehe, Petra; Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Flexible reassignment of flow processing-aware controllers in future wireless networks - Auroux, Sébastien; Karl, Holger (26th IEEE Annual International Symposium on Personal, Indoor, and Mobile Radio Communications, PIMRC 2015, Hong Kong, China, August 30 - September 2, 2015)

Efficient flow processing-aware controller placement in future wireless networks - Auroux, Sébastien; Karl, Holger (2015 IEEE Wireless Communications and Networking Conference, WCNC 2015, New Orleans, LA, USA, March 9-12, 2015)

Specification of Complex Structures in Distributed Service Function Chaining Using a YANG Data Model - Dräxler, Sevil; Karl, Holger (CoRR)

Dynamic Backhaul Network Configuration in SDN-based Cloud RANs - Dräxler, Martin; Karl, Holger (CoRR)

Pipelines for Ad-hoc Large-scale Text Mining - Wachsmuth, Henning
Today's web search and big data analytics applications aim to address information needs~(typically given in the form of search queries) ad-hoc on large numbers of texts. In order to directly return relevant information instead of only returning potentially relevant texts, these applications have begun to employ text mining. The term text mining covers tasks that deal with the inference of structured high-quality information from collections and streams of unstructured input texts. Text mining requires task-specific text analysis processes that may consist of several interdependent steps. These processes are realized with sequences of algorithms from information extraction, text classification, and natural language processing. However, the use of such text analysis pipelines is still restricted to addressing a few predefined information needs. We argue that the reasons behind are three-fold: First, text analysis pipelines are usually made manually in respect of the given information need and input texts, because their design requires expert knowledge about the algorithms to be employed. When information needs have to be addressed that are unknown beforehand, text mining hence cannot be performed ad-hoc. Second, text analysis pipelines tend to be inefficient in terms of run-time, because their execution often includes analyzing texts with computationally expensive algorithms. When information needs have to be addressed ad-hoc, text mining hence cannot be performed in the large. And third, text analysis pipelines tend not to robustly achieve high effectiveness on all texts, because their results are often inferred by algorithms that rely on domain-dependent features of texts. Hence, text mining currently cannot guarantee to infer high-quality information. In this thesis, we contribute to the question of how to address information needs from text mining ad-hoc in an efficient and domain-robust manner. We observe that knowledge about a text analysis process and information obtained within the process help to improve the design, the execution, and the results of the pipeline that realizes the process. To this end, we apply different techniques from classical and statistical artificial intelligence. In particular, we first develop knowledge-based approaches for an ad-hoc pipeline construction and for an optimal execution of a pipeline on its input. Then, we show theoretically and practically how to optimize and adapt the schedule of the algorithms in a pipeline based on information in the analyzed input texts in order to maximize execution efficiency. Finally, we learn patterns in the argumentation structures of texts statistically that remain strongly invariant across domains and that, thereby, allow for more robust analysis results in a restricted set of tasks. We formally analyze all developed approaches and we implement them as open-source software applications. Based on these applications, we evaluate the approaches on established and on newly created collections of texts for scientifically and industrially important text analysis tasks, such as financial event extraction and fine-grained sentiment analysis. Our findings show that text analysis pipelines can be designed automatically, which process only portions of text that are relevant for the information need at hand. Through scheduling, the run-time efficiency of pipelines can be improved by up to more than one order of magnitude while maintaining effectiveness. Moreover, we provide evidence that a pipeline's domain robustness substantially benefits from focusing on argumentation structure in tasks like sentiment analysis. We conclude that our approaches denote essential building blocks of enabling ad-hoc large-scale text mining in web search and big data analytics applications.

Challenges for Model-Integrating Components - Derakhshanmanesh , Mahdi; Ebert , Jürgen; Grieger, Marvin (Proceedings of the 2nd International Workshop on Model-Driven Engineering for Component-Based Software Systems co-located with ACM/IEEE 18th International Conference on Model Driven Engineering Languages & Systems (MoDELS 2015))

On Enabling Technologies for Longevity in Software - Derakhshanmanesh , Mahdi; Grieger, Marvin (Gemeinsamer Tagungsband der Workshops der Tagung Software Engineering 2015)

On the Need for Transactional Models@Run.Time - Derakhshanmanesh , Mahdi; Grieger , Marvin; Ebert, Jürgen (Proceedings of the 10th Workshop on Models@run.time co-located with 18th International Conference on Model Driven Engineering Languages and Systems (MODELS 2015))

Perceived Autonomy in the First Semester of Mathematics Studies - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the Ninth Congress of the European Society for Research in Mathematics Education)

Initiative Bottom-Up-Nachtreffen zum Doktorandenkolloquium der GDM - Braun, Eileen Angélique; Liebendörfer, Michael; Schorcht, Sebastian (Mitteilungen der Gesellschaft für Didaktik der Mathematik)

Multiobjective Optimization of the Flow Around a Cylinder Using Model Order Reduction - Peitz, Sebastian; Dellnitz, Michael (PAMM)
n this article an efficient numerical method to solve multiobjective optimization problems for fluid flow governed by the Navier Stokes equations is presented. In order to decrease the computational effort, a reduced order model is introduced using Proper Orthogonal Decomposition and a corresponding Galerkin Projection. A global, derivative free multiobjective optimization algorithm is applied to compute the Pareto set (i.e. the set of optimal compromises) for the concurrent objectives minimization of flow field fluctuations and control cost. The method is illustrated for a 2D flow around a cylinder at Re = 100.

„Career Planning for dynamic Economies" – Individualisierung und Neue Medien als Anknüpfungspunkt für berufliche Orientierung im Rahmen des EU geförderten Projekts SELFIE - Beutner, Marc; Rose, S (Wirtschaft und Erziehung)

Open Educational Resources in der aktuellen Bildungslandschaft: Motivation zur Teilung und Nutzung - Beutner, Marc; Schneider, J. N. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Förderung von Berufsorientierung, Basiskompetenzen und Ausbildungsreife als Herausforderung von Bildungsgangarbeit in Bildungsgängen der beruflichen Grundbildung - Beutner, Marc; Rose, S (Individuelle Kompetenzentwicklungswege – Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Medienkompetenz im Kontext beruflicher Orientierung - Beutner, Marc; Rose, M (Individuelle Kompetenzentwicklungswege – Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Gewaltprävention als Herausforderung für die Bildungsgangarbeit - Beutner, Marc; Rohde, S (Individuelle Kompetenzentwicklungswege – Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Jürs-Munby, K. / Carroll, J. / Giles, S. (Hg.): Postdramatic Theatre and the Political - Tönnies, Merle (Journal of Contemporary Drama in English)

Braucht die Medienbildung Impulse aus der Informatik? – Erkenntnisse aus interdisziplinären Seminaren - Klar, Tilman-Mathies; Engbring, Dieter (Digitale Medien und Interdisziplinarität, Herausforderungen, Erfahrungen, Perspektiven)

An Architecture for Energy-aware On-demand Mobile Network Management - Peuster, Manuel; Karl, Holger (Proceedings of the 5th Workshop on All Things Cellular: Operations, Applications and Challenges)
The increasing amount of mobile traffic leads to a significantly higher energy consumption of mobile networks that is mainly caused by the high number of required base stations. One recent solution for this is based on a two-layered network that uses long-range macro cells to provide a full coverage signaling overlay and short-range small cells for fast data transmissions. These small cells can be switched off when they are not needed and allow network-wide energy optimizations. This paper presents an architecture that extends existing mobile networks to integrate a small cell layer that supports on-demand cell activation. We discuss how additional small cells can be interconnected with existing core components and how they can be controlled by a resource management component. Finally, a Wi-Fi based proof of concept testbed implementation is presented that demonstrates the feasibility of the approach.

Improving the cleaning process in copper wire bonding by adapting bonding parameters - Althoff, Simon; Unger, Andreas; Sextro, Walter; Eacock, Florian (2015 17th Electronics Packaging Technology Conference)
Changing manufacturing technologies or material in well-known processes has to be followed by an adaption of process parameters. In case of the transition from aluminum wire to copper wire in heavy wire bonding, the adaption effort is high due to the strongly different mechanical properties of the wire. One of these adaption aspects, apart from wire material, is the existent oxide layers on wire and substrate. The ductile aluminum oxide is not influencing the bonding process much, because it is supposed to break apart in case of plastic deformation. The lubricating copper oxide layer has to be removed before micro welds can develop. Therefore, in this paper, experiments are carried out at low frequency to determine the friction energy needed to abrade the copper oxide layer of wire and substrate, which is indicated by an increase in the resulting friction coefficient. The friction energy per contact area to remove the interfering layers at low frequency is compared to the real bonding process working at 58 kHz. In addition, a theoretical concept is being described to get a grasp of the occurring mechanism. In the end a proposal is given how to set bonding parameters to get the cleanest surfaces with the installed bond tool.

Kavitationsdetektion mittels Self-Sensing-Ultraschallwandler - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (tm - Technisches Messen)
Eine Vielzahl von Prozessen in der Chemie und Verfahrenstechnik kann durch Ultraschall positiv beeinflusst werden. Oftmals ist ultraschallinduzierte Kavitation der Hauptwirkmechanismus für die positiven Effekte der Beschallung. Daher ist es notwendig die Kavitationsaktivität während des Prozesses zu quantifizieren um die Beschallung für den jeweiligen Prozess optimal gestalten und überwachen zu können. Eine Möglichkeit der prozessbegleitenden Kavitationsdetektion ist die Auswertung der akustischen Emissionen von oszillierenden und kollabierenden Kavitationsblasen mittels Drucksensoren in der Flüssigkeit. Raue Prozessrandbedingungen wie hohe Temperaturen oder aggressive Flüssigkeiten erschweren es jedoch geeignete Sensoren zu finden. Als Alternative wurde daher die Nutzbarkeit der Rückwirkung von Kavitationsereignissen auf das elektrische Eingansgssignal des Ultraschallwandlers zur Quantifizierung von Kavitation untersucht. Die experimentelle Analyse hat ergeben, dass das Einsetzen und in einigen Fällen auch die Art der Kavitation auf Basis der Rückwirkung auf das Stromsignal des Ultraschallwandlers bestimmt werden kann. Die Stärke der Kavitation war hingegen nicht aus den Stromsignalen abzuleiten.
Keywords: Kavitationsdetektion; Self-Sensing; So- nochemie; Ultraschallwandler

Integrierte Modellierung der Dynamik und der Verlässlichkeit komplexer mechatronischer Systeme - Kaul, Thorben; Meyer, Tobias; Sextro, Walter (10. Paderborner Workshop Entwurf mechatronischer Systeme)
Die starke Integration von Sensorik, Aktorik, Hard- und Software stellt Herausforderungen an die Verlässlichkeit intelligenter mechatronischer Systeme dar. Diese Systeme verfügen aber auch über großes Potential zur Verbesserung ihrer Verlässlichkeit durch eine Anpassung des Systemverhaltens an den aktuellen Zustand. Um den Umfang der Systemmodelle zu reduzieren und die Anpassung des Systemverhaltens zu ermöglichen, sind fortschrittliche Modellierungsmethoden notwendig, mit denen die Verlässlichkeit in frühen Phasen des Entwicklungsprozesses sichergestellt und evaluiert werden kann. Von den Attributen der Verlässlichkeit ist insbesondere die Zuverlässigkeit in hohem Maße von den auftretenden Belastungen an den Komponenten und damit vom dynamischen Systemverhalten abhängig. Bisherige Modellierungsansätze bilden diese Abhängigkeit nur unzureichend ab. Es wird daher ein Ansatz zur integrierten Modellierung mechatronischer Systeme vorgestellt. Dieser ist in der Lage, sowohl die Dynamik als auch die Zuverlässigkeit des Systems abzubilden. Die Transformation eines Modells des dynamischen Systemverhaltens generiert dabei ein Zuverlässigkeitsmodell. Für typischerweise konkurrierende Ziele können mit Hilfe von Mehrzieloptimierungsverfahren Betriebspunkte eines Systems bestimmt werden. Das integrierte Modell kann zur Erzeugung von Zielfunktionen für die Dynamik als auch für die Zuverlässigkeit genutzt werden. Die Ergebnisse ermöglichen eine Verhaltensanpassung durch Wahl eines paretooptimalen Betriebspunkts während des Betriebs. Das vorgeschlagene Konzept zur integrierten Modellierung mechatronischer Systeme bietet aufgrund des modellbasierten Entwicklungsansatzes und der automatisierten Transformation eines Verlässlichkeitsmodells eine Reduktion der Benutzereingaben und eine Entlastung des Benutzers. Dadurch wird die Wahrscheinlichkeit von Benutzerfehlern gesenkt und die Verlässlichkeit bereits während der Entwicklung erhöht. Somit können Iterationsschleifen vermieden und die Entwicklungskosten gesenkt werden.
Keywords: Verlässlichkeit; Zuverlässigkeit; Dynamik; integrierte Modellierung

Integrated Model for Dynamics and Reliability of Intelligent Mechatronic Systems - Kaul, Thorben; Meyer, Tobias; Sextro, Walter (European Safety and Reliability Conference (ESREL2015))
Intelligent mechatronic systems are able to autonomously adapt system behavior to current environmental conditions and to system states. To allow for such reactions, complex sensor and actuator systems as well as sophisticated information processing are required, making these systems increasingly complex. However, with the risk of increased system complexity also comes the chance to adapt system behavior based on current reliability and in turn to increase reliability. The adaptation is based on switching selecting an appropriate working point at runtime. Multiple suitable working points can be found using multi-objective optimization techniques, which require an accurate system model including system reliability. At present, modeling of system reliability is a laborious manual task performed by reliability modelling experts. Despite actual system reliability being highly dependent on system dynamics, pre-existing system dynamics models and the resulting reliability model are at best loosely coupled. To allow for closer interaction among dynamics and reliability model and to ensure these are always synchronized, advanced modeling techniques are required. Therefore, an integrated model is introduced that reduces user input to a minimum and that integrates system dynamics and system reliability.

Comparison and ensemble of temperature-based and vibration-based methods for machinery prognostics - Kimotho, James Kuria; Sextro, Walter (Annual Conference of the Prognostics and Health Management Society 2015)
This paper presents a comparison of a number of prognostic methods with regard to algorithm complexity and performance based on prognostic metrics. This information serves as a guide for selection and design of prognostic systems for real-time condition monitoring of technical systems. The methods are evaluated on ability to estimate the remaining useful life of rolling element bearing. Run-to failure vibration and temperature data is used in the analysis. The sampled prognostic methods include wear-temperature correlation method, health state estimation using temperature measurement, a multi-model particle filter approach with model parameter adaptation utilizing temperature measurements, prognostics through health state estimation and mapping extracted features to the remaining useful life through regression approach. Although the performance of the methods utilizing the vibration measurements is much better than the methods using temperature measurements, the methods using temperature measurements are quite promising in terms of reducing the overall cost of the condition monitoring system as well as the computational time. An ensemble of the presented methods through weighted average is also introduced. The results show that the methods are able to estimate the remaining useful life within error bounds of +-15%, which can be further reduced to +-5% with the ensemble approach.
Keywords: ensemble methods; combined prognostics; data fusion

Thick KNbO 3 films deposited by ultrasonic-assisted hydrothermal method - Kudo, Ryo; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Acoustical Science and Technology)

Advantages of reliability-adaptive system operation for maintenance planning - Meyer, Tobias; Kaul, Thorben; Sextro, Walter (Proceedings of the 9th IFAC Symposium on Fault Detection, Supervision and Safety for Technical Processes)
Intelligent mechatronic systems other the possibility to adapt system behavior to current dependability. This can be used to assure reliability by controlling system behavior to reach a pre-defined lifetime. By using such closed loop control, the margin of error of useful lifetime of an individual system is lowered. It is also possible to change the pre-defined lifetime during operation, by adapting system behavior to derate component usage. When planning maintenance actions, the remaining useful lifetime of each individual system has to be taken into account. Usually, stochastic properties of a fleet of systems are analyzed to create maintenance plans. Among these, the main factor is the probability of an individual system to last until maintenance. If condition-based maintenance is used, this is updated for each individual system using available information about its current state. By lowering the margin of error of useful lifetime, which directly corresponds to the time until maintenance, extended maintenance periods are made possible. Also using reliability-adaptive operation, a reversal of degradation driven maintenance planning is possible where a maintenance plan is setup not only according to system properties, but mainly to requirements imposed by maintenance personnel or infrastructure. Each system then adapts its behavior accordingly and fails according to the maintenance plan, making better use of maintenance personnel and system capabilities at the same time. In this contribution, the potential of maintenance plan driven system behavior adaptation is shown. A model including adaptation process and maintenance actions is simulated over full system lifetime to assess the advantages gained.
Keywords: Adaptive systems; Reliability analysis; Availability; Adaptive control; Maintenance; Self-optimizing systems; Self-optimizing control; Stochastic Petri-nets

Anforderungen an Condition-Monitoring-Verfahren zur Nutzung im zuverläsigkeitsgeregelten Betrieb adaptiver Systeme - Meyer, Tobias; Kimotho, James Kuria; Sextro, Walter (27. Tagung Technische Zuverlässigkeit (TTZ 2015) - Entwicklung und Betrieb zuverlässiger Produkte)
Intelligente technische Systeme, die in der Lage sind, sich an geänderte Umgebungsbedingungen anzupassen, ermöglichen eine Adaption anhand der aktuell erreichten Zuverlässigkeit. Zu diesem Zwecke kann ein geschlossener Regelkreis formuliert werden, der dazu geeignet ist, den Betriebspunkt des Systems während der gesamten Lebensdauer anzupassen. Dadurch wird eine harte Umschaltung während des Betriebs vermieden und die Verhaltensanpassung ist vom Nutzer weitgehend unbemerkt möglich. Dazu wird die aktuelle Restlebensdauer mit einer vorgegebenen Restlebensdauer verglichen. Durch Änderung der vorgegebenen Restlebensdauer lässt sich auch eine Anpassung der gewünschten Nutzungsdauer erreichen, beispielsweise um veränderte Wartungsintervalle einzuhalten. Zu diesem Zwecke ist es allerdings notwendig, die aktuell erreichte Zuverlässigkeit zu schätzen. Für die Regelung ist dabei die aktuelle Restlebensdauer der wichtigste Parameter, da er als Istwert direkt mit der gewünschten Restlebensdauer als Sollwert verglichen wird und als Reglereingang dient. Für die Genauigkeit der Regelung ist daher die Bestimmung der Restlebensdauer von entscheidender Bedeutung. Es wird ein Modell des Regelkreises vorgestellt, das auch den Einfluss einer fehlerhaften Restlebensdauerschätzung auf die Verhaltensanpassung abbildet. Dadurch ist es möglich, Grenzen der Verhaltensanpassung und die zur Einhaltung notwendige Genauigkeit der Restlebensdauerschätzung zu bestimmen. Es gibt zahlreiche Ansätze, die Restlebensdauer zu schätzen, die aufgeteilt werden in modellbasierte Verfahren und datengetriebene Verfahren. Die individuelle Eignung eines jeden Verfahrens sowie die Modellbildung oder die Nutzung geeigneter Algorithmen ist stark systemabhängig. Um die Auswahl von Verfahren und Modellen oder Algorithmen zu ermöglichen, werden zunächst die Anforderungen an die Restlebensdauerschätzung zur Nutzung als Regelungs-Istwert bestimmt. Verschiedene Verfahren werden sodann hinsichtlich ihrer Eignung evaluiert und Anwendungsgrenzen aufgezeigt.

Modeling and simulation of the ultrasonic wire bonding process - Meyer, Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (2015 17th Electronics Packaging Technology Conference)
Ultrasonic wire bonding is an indispensable process in the manufacturing of semiconductor components. It is used for interconnecting the silicon die to e.g. connectors in the housing or to other semiconductors in complex components. In high power applications, such as wind turbines, locomotives or electric vehicles, the thermal and mechanical limits of interconnects made from aluminum are nearing. The limits could be overcome using copper wire bonds, but their manufacturing poses challenges due to the harder material, which leads to increased wear of the bond tools and to less reliable production. To overcome these drawbacks, adaptation of process parameters at runtime is employed. However, the range of parameter values for which a stable process can be maintained is very small, making it necessary to compute suitable parameters beforehand. To this end, and to gain insights into the process itself, the ultrasonic bonding process is modeled. The full model is composed of several partial models, some of which were introduced before. This paper focuses on the modularization of the full model and on the interaction of partial models. All partial models are presented, their interaction is shown and the general outline of the simulation process is given.

A Mechanical Model for the Dynamical Contact of Elastic Rough Bodies with Viscoelastic Properties - Schulte, Frank; Neuhaus, Jan; Sextro, Walter (Proceedings of ICoEV 2015 International Conference on Engineering Vibration)
The contact between viscoelastic materials e.g. elastomers and a rough surface leads to a special friction characteristic, which differs greatly in its properties comparing to other materials like metals. In practice, this friction combination occurs for example in the tire-road contact, or in the use of rubber gaskets. Due to the frictional forces a system is significantly influenced in its vibrational properties. The friction force is composed of two main components adhesion and hysteresis. The adhesion results from molecular bounds between the contact partners, while the deformation of the viscoelastic material by the roughness of the counter body leads to power loss. This internal friction results in an additional frictional force, which is described by the hysteresis. To simulate the frictional behaviour of elastomers on rough surfaces and thus to determine the energy dissipation in contact, it is necessary to develop a mechanical model which considers the roughness of the contact partners, as well as dynamic effects and the dependence on normal pressure and sliding speed. The viscoelastic material behaviour must also be considered. The contact between two rough surfaces is modelled as a rough rigid layer contacting a rough elas- tic layer. The elastic layer is modelled by point masses connected by Maxwell-elements. This allows the viscoelastic properties of the elastomer to be considered. The behaviour of whole system can be described by equations of motion with integrated constraints. The degrees of freedom of the model depends on the varying contact conditions. A point mass not in contact has two degrees of freedom. A point mass in contact moving along the roughness path can be described by only one degree of freedom. For each Maxwell-Element also an inner coordinate and thus a further degree of freedom is needed. Because of varying contact conditions dur- ing the simulation, the simulation interrupts in case the contact conditions change. Then the equations of motions are adapted with respect to the contact constraints. As a result of the simulation one obtain the energy dissipation and thus the friction char- acteristic during the friction process. It is possible to use these results in three dimensional point-contact elements in order to model contact surfaces on lager length scales.
Keywords: Contact Mechanics; Viscoelastic Material; Adhesive Friction; Hysteresis Friction; Energy Dissipation; Vibration

Modeling of the Stick-Slip Effect in Heavy Copper Wire Bonding to Determine and Reduce Tool Wear - Unger, Andreas; Sextro, Walter; Meyer, Tobias; Eichwald, Paul; Althoff, Simon; Eacock, Florian; Brökelmann, Michael (2015 17th Electronics Packaging Technology Conference)
To increase quality and reliability of copper wire bonds, self-optimization is a promising technique. For the implementation of self-optimization for ultrasonic heavy copper wire bonding machines, a model of stick-slip motion between tool and wire and between wire and substrate during the bonding process is essential. Investigations confirm that both of these contacts do indeed show stick-slip movement in each period oscillation. In a first step, this paper shows the importance of modeling the stick-slip effect by determining, monitoring and analyzing amplitudes and phase angles of tool tip, wire and substrate experimentally during bonding via laser measurements. In a second step, the paper presents a dynamic model which has been parameterized using an iterative numerical parameter identification method. This model includes Archard's wear approach in order to compute the lost volume of tool tip due to wear over the entire process time. A validation of the model by comparing measured and calculated amplitudes of tool tip and wire reveals high model quality. Then it is then possible to calculate the lifetime of the tool for different process parameters, i.e. values of normal force and ultrasonic voltage.

Minimizing Expectation Plus Variance - Monien, Burkhard; Mavronicolas, Marios (Theory of Computing Systems)
We consider strategic games in which each player seeks a mixed strategy to minimize her cost evaluated by a concave valuation V (mapping probability distributions to reals); such valuations are used to model risk. In contrast to games with expectation-optimizer players where mixed equilibria always exist (Nash 1950; Nash Ann. Math. 54, 286–295, 1951), a mixed equilibrium for such games, called a V-equilibrium, may fail to exist, even though pure equilibria (if any) transfer over. What is the exact impact of such valuations on the existence, structure and complexity of mixed equilibria? We address this fundamental question in the context of expectation plus variance, a particular concave valuation denoted as RA, which stands for risk-averse; so, variance enters as a measure of risk and it is used as an additive adjustment to expectation. We obtain the following results about RA-equilibria:A collection of general structural properties of RA-equilibria connecting to (i) E-equilibria and Var-equilibria, which correspond to the expectation and variance valuations E and Var, respectively, and to (ii) other weaker or incomparable properties such as Weak Equilibrium and Strong Equilibrium. Some of these structural properties imply quantitative constraints on the existence of mixed RA-equilibria.A second collection of (i) existence, (ii) equivalence and separation (with respect to E-equilibria), and (iii) characterization results for RA-equilibria in the new class of player-specific scheduling games. We provide suitable examples with a mixed RA-equilibrium that is not an E-equilibrium and vice versa.A purification technique to transform a player-specific scheduling game on two identical links into a player-specific scheduling game on two links so that all non-pure RA-equilibria are eliminated while no new pure equilibria are created; so, a particular player-specific scheduling game on two identical links with no pure equilibrium yields a player-specific scheduling game with no RA-equilibrium (whether mixed or pure). As a by-product, the first PLS-completeness result for the computation of RA-equilibria follows.

RSDL workbench results for OAEI 2015 - Schwichtenberg, Simon; Engels, Gregor (Proceedings of the 10th International Workshop on Ontology Matching collocated with the 14th International Semantic Web Conference (ISWC 2015), Bethlehem, PA, USA, October 12, 2015.)

Self-assembled nanogap electrodes for the directed assembly of nanoparticles - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

Self-assembled Nanogap Electrodes in Microﬂuidic Channels - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

Three-dimensional analysis of mask-clogging effects on the morphology of nanoparticles fabricated by nanosphere lithography - Brodehl, Christoph; Riedl, Thomas; Greulich-Weber, Siegmund; Lindner, Jörg

How to create billions of tailored plasmonic nanoparticles in half an hour - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

Correlation between defect densities in colloidal nanosphere masks and experimental parameters - Drude, Dennis; Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

An Algorithm for Tailoring of Nanoparticles by Double Angle Resolved Nanosphere Lithography - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg (MRS Proceedings)

Investigation of cubic GaN quantum dots grown by the Stranski-Krastanov process - Bürger, M.; Lindner, Jörg; Reuter, Dirk; As, D. J. (physica status solidi (c))
We investigate the formation of cubic GaN quantum dots (QDs) on pseudomorphic strained cubic AlN layers on 3C-SiC (001) substrates grown by means of molecular beam epitaxy. Surface morphologies of various QD sizes and densities were obtained from uncapped samples by atomic force microscopy. These results were correlated with similar but capped samples by photoluminescence experiments. The QD density varies by one order of magnitude from ~1x10^10 cm^-2 to ~1x10^11 cm^-2 as a function of the GaN coverage on the surface. The initial layer thickness for the creation of cubic GaN QDs on cubic AlN was obtained to 1.95 monolayers by a comparison between the experimental results and an analytical model. Our results reveal the strain-driven Stranski-Krastanov growth mode as the main formation process of the cubic GaN QDs.

Self-Arrangement of Colloidal Au Nanoparticles in SiO2-Nanopores fabricated by Block-Copolymer Lithography - Garozzo, C.; Brassat, Katharina; La Magna, A.; Puglisi, R.A.; Lindner, Jörg

STEM-CL investigations on the influence of stacking faults on the optical emission of cubic GaN epilayers and cubic GaN/AlN multi-quantum wells - Kemper, R. M.; Veit, P.; Mietze, C.; Dempewolf, A.; Wecker, T.; Bertram, F.; Christen, J.; Lindner, Jörg; As, D. J. (physica status solidi (c))
We report the influence of {111} stacking faults on the cathodoluminescence (CL) emission characteristics of cubic GaN (c-GaN) films and cubic GaN/AlN multiquantum wells. Transmission electron microscopy (TEM) measurements indicate that stacking faults (SFs) on the {111} planes are the predominant crystallographic defects in epitaxial films, which were grown on 3CSiC/ Si (001) substrates by plasma-assisted molecular beam epitaxy. The correlation of the SFs and the luminescence output is evidenced with a CL setup integrated in a scanning TEM (STEM). By comparing the STEM images and the simultaneously measured CL signals it is demonstrated that SFs in these films lead to a reduced CL emission intensity. Furthermore, the CL emission intensity is shown to increase with increasing film thickness and decreasing SF density. This correlation can be connected to the reduction of the full width at half maximum of X-ray diffraction rocking curves with increasing film thickness of c-GaN films.

Stability of heteroepitaxial coherent growth modes on nanowire radial surfaces - Riedl, Thomas; Lindner, Jörg